Experience in production of 18F isotope in the Cyclone-30 for synthesis of fluorinated radiopharmaceuticals (International Journal of Biology and Chemistry, 2022)
This article provides a brief overview of the 18F isotope production using the Cyclone-30 cyclotron and two liquid targets with the volume of 0.5 and 2.0 ml, water enriched with the 18O isotope was used as the target material. The obtained isotope was used for serial production of the [18F]FDG radiopharmaceutical and supply of this medicine to the operating PET centers in Almaty. The isotope was also used for experimental syntheses of [18F]PSMA-1007 and Na[18F]F to assess the possibility of implementation these medicines into the production and medical practice of the Republic of Kazakhstan. The need for the implementation of [18F]PSMA-1007 is associated with the problem of early diagnosis and control of prostate cancer treatment, and Na[18F]F - with the earliest possible detection of bone metastases in malignant tumors of various localization. This paper provides the average radiochemical yield and the main quality parameters for [18F]FDG, [18F]PSMA-1007 and Na[18F]F. This scientific and practical work allows us to evaluate the three-year production experience and the possibilities of fluorine production by reaction (p,n) on the cyclotron С-30, and also reflects the prospects of using fluorine in the development of new-generation radiopharmaceuticals for the diagnosis of oncological diseases.